My father's house : a novel - Kvensler, Ulf, 1968- (Hanover Square Press, 2025)
"Isak works in home care in a small town in Sm̊aland. One day, he is contacted by his father, an internationally known artist, who left Isak when he was a child. His father is dying, and his only wish is to reconcile what remains of their relationship as father and son. He promises Isak his fortune, but Isak has certain reservations. Alongside his girlfriend, Madde, Isak decides to visit his father, but the line between nightmare and reality blurs as family secrets unravel."--